Archivist and Librarian Training at the University of Costa Rica (UCR): so close and so distant - Jaén García, Luis Fernando (2018)
In the framework of the fiftieth anniversary of the creation of the School of Library and Information Sciences of the University of Costa Rica (UCR), I join the parabienes for half a century of existence of this Academic Unit